Cerebral rheumatoid vasculitis: an integrated analysis of case presentation, literature review, and prognostic stratification - Zhang, Yinghui; Zhai, Xuefeng; Ning, Li; Yang, Juan; Yang, Liu; Li, Jian; Chi, Shuhong; Ma, Boya; Lu, Liu; Li, Zhao; Xiao, Yang (Frontiers in Immunology, 2025)
This study integrated a comprehensive literature review spanning from 1951 to 2025 with a histologically confirmed case of cerebral rheumatoid vasculitis (CRV) in order to improve the management of this rare and severe complication of rheumatoid arthritis (RA). By analyzing 37 CRV cases, we observed a striking decline in mortality after the 1980s, with an odds ratio (OR) of 33.07. The combination of immunosuppressants and corticosteroids significantly enhanced treatment outcomes, showing 81.8% efficacy compared to a 63.6% mortality rate without immunosuppressants. Based on these findings, we developed the CRV diagnostic workflow to aid early detection. Our results emphasize the importance of vigilance for neurological symptoms in RA patients and highlight the need for future research to optimize treatment protocols and reduce long-term disability.